The Effect Of Leadership Style, Communication, Discipline, And Public Service On Community Participation In Paying Waste Retribution At The Environmental Agency - Samudra Kurniaman Zendrato (International Journal Labs, 2025)
The waste levy is part of the original regional income, in order for the community to pay the waste levy, it is necessary to have the influence of leaders with a leadership style, good communication, discipline and public service that is directly felt by the community. This study aims to determine the Influence of Leadership Style on Community Participation in Paying Waste Levy. Data analysis using multiple linear regression model with a quantitative approach with a descriptive type of research using SPSS version 22.0 with a sample of 224 respondents. The results of the study showed that each variable X partially affected variable Y and simultaneously variable X affected variable Y. The conclusions of this study are 1) that there is an influence of Leadership Style on Community Participation in Paying Waste Levy; 2) that there is an influence of communication on Community Participation in Paying Waste Levy; 3) that there is an influence of work discipline on Community Participation in Paying Waste Levy; 4) that there is an influence of public services on Community Participation in Paying Waste Levy. 5) that the free variable simultaneously affects the bound variable together. Dependent variables (Leadership style, Communication, Work Discipline and Public Service) that can be explained by independent variables (Community Participation) are 52% while the remaining 48% are explained by other variables that are not studied.